Decadence and Military Overstretch: Modeling the Dynamics of National Decline - Yong Jin Kim (ZBW - Leibniz Information Centre for Economics, 2025)
The paper presents a theoretical model and its simulation to explore the process of the fall of nations by focusing on moral and cultural decline, as well as military overstretch. In the model, a representative agent divides his time among military spending, material production, the consumption of scientific ideas and that of religious ideas. Both religious and scientific capital accumulate through learning-by-doing mechanism of the consumption of religious ideas and that of scientific ideas, respectively, at the national level. `Religious' means `decadent' or `nonproductive emotional'. Scientific capital boosts income, while religious capital does not. And wealthier nations experience increased decadence and military overstretch, which in turn accelerates moral and cultural decline, increasing the growth rate of religious capital and reducing that of scientific capital and income. The pseudo saddle path with a higher substitutability between religious and scientific idea consumption leads to a steady state like equilibrium. But it endogenously forks into one of two extreme potential outcomes, a religion (decadence) dominated path with slow income growth or a science dominated path with rapid growth, based on the initial conditions and policies. Affluent nations with a high level of decadence or of military overstretch are more prone to rapid decline after peaking, forking into a religion dominated path with slow income growth. The paper suggests that effective policy interventions, such as reducing decadence and military overstretch, increasing the consumption of scientific ideas, and maintaining balanced military spending, could help guide nations toward a science dominated path with sustained growth. These policies could prevent nations from veering into a religion dominated path with slow income growth.
Keywords: 330; the rise and fall of nations; decadence; overstretch; saddle path equilibrium; learning by doing